2017
DOI: 10.1002/nau.23279
|View full text |Cite
|
Sign up to set email alerts
|

Time to and predictors of dual incontinence in older nursing home admissions

Abstract: Aims: There are few studies of nursing home residents that have investigated the development of dual incontinence, perhaps the most severe type of incontinence as both urinary and fecal incontinence occur. To determine the time to and predictors of dual incontinence in older nursing home residents. Methods: Using a cohort design, records of older nursing home admissions who were continent or had only urinary or only fecal incontinence (n = 39,181) were followed forward for report of dual incontinence. Four nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
3
17
1
Order By: Relevance
“…6 The prevalence of double incontinence (DI), both UI and fecal incontinence (FI), is high among individuals living in nursing homes, 7 and the significant predictors for the development of DI are pre-existing UI, greater functional or cognitive impairment, higher number of comorbidities, older age and lower quality of nursing home care. 8 In an Asian study, a higher Clinical Dementia Rating Score was considered a significant predictor of DI. 9 The management of incontinence is a heavy burden in society in terms of human and financial resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The prevalence of double incontinence (DI), both UI and fecal incontinence (FI), is high among individuals living in nursing homes, 7 and the significant predictors for the development of DI are pre-existing UI, greater functional or cognitive impairment, higher number of comorbidities, older age and lower quality of nursing home care. 8 In an Asian study, a higher Clinical Dementia Rating Score was considered a significant predictor of DI. 9 The management of incontinence is a heavy burden in society in terms of human and financial resources.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence (UI) is considered a geriatric syndrome, and is associated with multiple health‐related problems, including dermatitis, falls, lower activity of daily living (ADL), impairment of dignity and higher mortality . The prevalence of double incontinence (DI), both UI and fecal incontinence (FI), is high among individuals living in nursing homes, and the significant predictors for the development of DI are pre‐existing UI, greater functional or cognitive impairment, higher number of comorbidities, older age and lower quality of nursing home care . In an Asian study, a higher Clinical Dementia Rating Score was considered a significant predictor of DI .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, FI is not an inevitable consequence of old age or dementia alone, 2 but has multiple underlying factors, 14 some of which can be identified and treated. 15 In the older person, FI may be the consequence of age-related anorectal deficits such as reduced anal sphincter pressure; 16 it also may be underpinned by cognitive impairment, 17,18 length of nursing home stay, 10,19 diarrhea, 20 constipation, 10,17 or effects of polypharmacy. 21 When a cure is not achievable, incontinence management can produce "social continence" (incontinence well managed so that it is not socially evident), thus alleviating embarrassment and preserving the dignity of a person.…”
mentioning
confidence: 99%
“…In line with these previous findings and our new results about toileting difficulties, prevention of ADL decline and toileting difficulties should be of concern for those providing in-home care and also for healthcare planners. Toileting difficulties developed after admission to nursing home have also been previously addressed, and some studies have found that prevalence of toileting difficulties can rise in a few months to years after admission (Bliss, Gurvich, Eberly, & Harms, 2017;Boguth & Schenk, 2008;Ihnat et al, 2016;Saga, Vinsnes, Morkved, Norton, & Seim, 2013;Saxer, Halfens, de Bie, & Dassen, 2008). Concerning incontinence among residents established in nursing homes, prevalence is repeatedly reported to be high (Ihnat et al, 2016;Offermans, Du Moulin, Hamers, Dassen, & Halfens, 2009;Saga et al, 2013;Saga, Vinsnes, Morkved, Norton, & Seim, 2015;Saxer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning incontinence among residents established in nursing homes, prevalence is repeatedly reported to be high (Ihnat et al, 2016;Offermans, Du Moulin, Hamers, Dassen, & Halfens, 2009;Saga et al, 2013;Saga, Vinsnes, Morkved, Norton, & Seim, 2015;Saxer et al, 2008). The seemingly complex relation between toileting difficulties and nursing home residency has been widely investigated, and the value of mapping and combating incontinence associated with nursing home residency is still being emphasized (Bliss et al, 2017;Offermans et al, 2009;Saga et al, 2013Saga et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%